Improving the legal framework for state management in the economic sector - Nguyen Thi Hong Hanh (Journal of State Management, 2025)
State management is a fundamental and essential function of the state apparatus in all political systems. However, the current status of state economic management in Vietnam still faces numerous challenges, particularly the unclear delineation of authority and responsibility between central and local governments. To enhance the effectiveness of economic state management, Vietnam needs to continue improving its legal system toward consistency, transparency, and feasibility. Administrative procedure reforms should be accelerated to create a favorable investment and business environment while strengthening regulatory agencies' law enforcement capacity and accountability. Additionally, promoting international economic integration and improving investment attraction policies will help Vietnam better leverage development opportunities in the context of globalization. This article analyzes the current state of state economic management and proposes solutions to improve the legal framework for state management in this field.